Crucible of Conflict : Tamil and Muslim Society on the East Coast of Sri Lanka - McGilvray, Dennis B. (Book collections on Project MUSE., 2008)
Examines the caste, marriage patterns, ethnicity and religious institutions in the Tamil-speaking Hindu and Muslim communities situated along the eastern coastline of Sri Lanka, exploring the sources of their ethnic and political hostilities in the modern.